Immune activation in the course of HIV‐1 infection: Causes, phenotypes and persistence under therapy. Issue 2 (10th October 2015) - Younas, M; Psomas, C; Reynes, J; Corbeau, P
Abstract : Systemic immune activation is a striking consequence of HIV‐1 infection. Even in virologically suppressed patients, some hyperactivity of the immune system and even of the endothelium and of the coagulation pathway may persist. Apart from immune deficiency, this chronic activation may contribute to various morbidities including atherothrombosis, neurocognitive disorders, liver steatosis and osteoporosis, which are currently main challenges. It is therefore of major importance to better understand the causes and the phenotypes of immune activation in the course of HIV‐1 infection. In this review we will discuss the various causes of immune activation in HIV‐1 infected organisms: the presence of the virus together with other microbes, eventually coming from the gut, CD4+ T cell lymphopenia, senescence and dysregulation of the immune system, and/or genetic factors. We will also describe the activation of the immune system: CD4+ and CD8+ T cells, B cells, NKT and NK cells, dendritic cells, monocytes and macrophages, and neutrophils of the inflammation cascade, as well as of the endothelium and the coagulation system. Finally, we will see that antiretroviral therapy reduces the hyperactivity of the immune and coagulation systems and the endothelial dysfunction, but often does not abolish it. A better knowledge of this phenomenon might help us to identify biomarkers predictive of non AIDS‐linked comorbidities, and to define new strategies aiming at preventing their emergence.